ERGONOMIC APPROACH TO DESIGNING ADAPTIVE CLOTHING FOR REHABILITATION OF PATIENTS AFTER COVID-19 - Остапенко, Н. В.; Колосніченко, О. В.; Арабаджи, А. Г.; Скріпченко, А. Г.; Кузьменко, В. В.; Косточка, А. О. (Art and Design, 2023)
Purpose: to analyze and study the characteristic movements, postures and positions of the patient at the stage of rehabilitation after COVID-19 in order to design ergonomic adaptive clothing. Methodology. Visual-analytical, information-research approaches, methods of comparative and system-structural analysis were used. Results. The relevance of the design of modern ergonomic adaptive clothing has been shown. The characteristic movements, postures and positions of the patient during rehabilitation after COVID-19 are analyzed, described and graphically presented. The functional and structural elements of shoulder and waist clothing and recommendations for their use are described and characterized. Scientific novelty. Specific requirements for functional adaptive clothing and materials for its manufacture for patients undergoing rehabilitation after the disease have been developed. Elements of constructive and technological solutions for shoulder and waist clothing for patients in the rehabilitation period after COVID-19 have been systematized. Practical significance. The main postures and positions of the patient are graphically presented depending on the intensity of activity and postural drainage. The characteristic postures, movements and positions of the patient during rehabilitation after COVID-19 are described, summarized and graphically reproduced. Based on the study of a set of physical exercises for patients in rehabilitation after COVID-19, recommendations are given on the use of functional and structural elements of the front / legs, back, sleeves, trousers. The functional elements of the design and technological solution of ergonomic adaptive clothing are described and characterized.